Pemetaan Scientometrik Penelitian PBL pada Pendidikan Agama Islam Perguruan Tinggi: Analisis Jaringan Sitasi, Klaster Topik, dan Research Gap - Hamka, Buya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to identify research gaps and new directions for the development of the Problem-Based Learning (PBL) model in the context of Islamic Religious Education (IRE) at the university level. Using a scientometric approach based on bibliometric analysis, this study maps the trends, citation networks, and dominant themes in PBL-IRE research from 2013 to 2023. Data were collected from the Scopus and Google Scholar databases and then analyzed using VOSviewer and Python Google Colab software to generate maps of author networks, keywords, and institutional collaborations. The data analysis techniques used include quantitative descriptive analysis to calculate the number of publications per year and citation patterns, as well as co-occurrence of keywords and citation network analysis using VOSviewer. The results show a significant increase in publication volume since 2020, with a peak in 2023, indicating growing academic attention to problem-based pedagogical innovations in Islamic education. The analysis generated five main clusters: (1) the application of PBL in IRE, (2) project-based models in PBL, (3) the integration of Islamic values and critical thinking skills, (4) collaboration among authors and institutions, and (5) research gaps at the postgraduate level. Despite the increased intensity of research, international collaboration and postgraduate-based research remain low, indicating a future research development opportunity.